Investigações limnológicas e ictiológicas em Curuá-Una, a primeira represa hidrelétrica na Amazônia Central - Junk, Wolfgang Johannes; Robertson, Barbara A.; Darwich, Assad José; Vieira, Ivanzir (Acta Amazonica, 1981)
Curuâ-Una Reservoir is the first hydrelectric clam of the Amazon basin and is being studied by the Instituto Nacional de Pesquisas da Amazonia (INPA), Manaus, in agreement with the Centrais Elétricas Brasileiras S/A (ELETROBRAS) and the Centrais Elétricas do Pará (CELPA). Analyses of hydrochemical, aquatic macrophyte, zooplankton (Cladocera), and fish material colected April and May, 1978, in the reservoir show the following ecological situation. The Curuá-Una River and its tributaries belong, from a chemical point of view, to the complex "clear water" group, however the Curuá-Una\'s tributaries above the dam site, are very acid and extremly poor in mineral salts, while the Curuá-Una River itself presents a higher pH and a greater concentration of salts. The dilution effect of the tributaries in the Curuâ-Una River probably surmounts the local enriching effects of soil and vegetation drainage. No pronounced temperature or chemical stratification wore observed probably because of the low retention time of the water in the reservoir, 29,1 days, which resulted in a theoretical current velocity of aproximatly 100 m/hour. The reduction in oxygen between afluent and efluent is distinct but H2S was not observed during this sampling period. Great quantities of floating aquatic macrophytes occur in the reservoir and the principal species are Eichhornia crassipes, Scirpus cubensis, Pistia stratiotes and Paspalum repens. The abundance and distribution of the plants show clear relationships with the chemical situation of the reservoir as well as with the history of the inundation period. 34 species of Cladocera belonging to 6 families were identified, however, the density of animals was very low. The distribution and standing-stock of Cladocera show differences between the collecting sites as well as a vertical stratification, 3 species, Bosminopsis deitersi, Ceriodaphnia cornuta and Ceriodaphnia reticulata, represented 53% - 99% of the total number of specimens. 62 species of fish, belonging to 14 families were collected. Some species showed preference for the reservoir area while others were found predominantly above or below. The frequency of the "piranhas" was two times greater in the reservoir while members of the Auchenipteridae were more frequent outside the reservoir. Clupeidae were found only below the dam site. The total quantitly of fish was relatively low as many specimens were small.